Perception of nursing students and faculty on problem based learning - Awale, Shanti; KC, Sarala; Pun, Khagi Maya; Panthee, Bimala; Maharjan, Babu Raja (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Problem-based learning (PBL) is an active learning technique where learning takes place through solving real-problems that facilitates lifelong learning. Nursing as well as medical students have considered PBL method to be more interesting as compared to conventional teaching. Implementation of problem based method of learning in nursing curriculum is new and the first of its kind in context of Nepal. Thus, this study aimed to find out the perception on PBL among nursing students and faculty.Method: A cross-sectional analytical study was conducted in May-Jun 2023 to assess the perception on PBL among 143 bachelor of nursing students and 20 nursing faculty who were involved in PBL sessions of PAHS, School of Nursing and Midwifery. A convenience sampling was employed through online Google form. The Statistical Package for Social Sciences (SPSS) was used to analyze data.Result: Out of 143 students, 65(45.45%) were first year students and 78(54.55%) were second year students. Regarding perception on PBL, 137(95.80%) of students and 19(95.00%) faculty had positive perception. The highest mean score for the student (3.32±0.68) was found on the statement “PBL promotes students’ self-directed learning on the topic”. Likewise, the highest mean score (3.55±0.51) for the faculty perception was on the statement “PBL promotes students’ participation in the learning process”.Conclusion: This study shows the students and faculty had positive perception on PBL as a teaching learning methods in bachelor level nursing program.